Household clean and healthy living behaviors and stunting severity among children under five in Indonesia: A cross-sectional study - Maghfirah, Dhiyal; Safri, Mulya; Maharani, Cut R.; Yusuf, Sulaiman; Sofia, Sofia (Narra Sains Indonesia, 2025)
The prevalence of stunting among children under five in Indonesia reached 21.5% in 2023, underscoring a persistent public health challenge. Behavioral factors, including Clean and Healthy Living Behavior (CHLB), are known to influence health outcomes and may contribute to child growth. The aim of this study was to examine the association between household CHLB and stunting severity among children under five years of age. A cross-sectional study was conducted from September to October 2024 in the Sukajaya Primary Health Center area. Using a total sampling technique, 62 mothers of stunted children aged 0–59 months were recruited. Data were collected through direct interviews using structured questionnaires and anthropometric measurements of children’s height and weight. Statistical analysis included chi-square tests and multivariable logistic regression using SPSS version 23.0. The results showed that children with severe stunting were significantly younger than those with moderate stunting (26.9±14.9 months, p<0.001). Overall, household CHLB implementation was suboptimal; however, no statistically significant association was identified between the overall CHLB and stunting severity (p=0.091). Multivariable analysis identified child age (OR=0.916, p=0.001) based on weight-for-age z-scores (OR=0.298; p=0.019) as an independent predictor of stunting severity, whereas household CHLB was not significantly associated (p=0.132). In conclusion, stunting severity among children under five was primarily associated with child age and nutritional status rather than household CHLB implementation. These findings highlight the importance of early-life nutritional interventions to prevent progression to severe stunting.